PENDEKATAN TEORITIS ANALISIS SUMBER-SUMBER INFLASI - Manurung, Jonni (UNIKA Santo Thomas, 2011)
The Theory Approach of Inflation Determinant Analysis has the goal to identify the sources of inflation and finding the alternative policy strategy to stabilizing the inflation. According to the inflation decomposition, the source of inflation is core or underlying inflation, noncore inflation, and noise inflation. According to the expected-augmented Phillips curve, the deviation of inflation to the expected inflation is sourced from supply shocks, the deviation of economic growth rate to the natural rate, and the deviation of unemployment rate to the natural rate. According to the dynamic monetary policy inconsistent, inflation is sourced from inflation target, the deviation of economic growth rate to natural rate, the deviation of unemployment rate to natural rate, and supply shock. According to the credibility monetary policy, inflation is sourced from expected inflation and the deviation of economic growth rate to natural rate. According to the inflation composition, the deviation of inflation to expected inflation is sourced from noncore inflation and noise inflation. So that the relation between the expected-augmented Phillips curvel, the dynamic monetary policy inconsistent, and the credibility monetary policy is show that the noncore inflation and the noise inflation determined by the deviation of economic growth rate to natural rate, the deviation of unemployment rate to natural rate, and supply shock. The conclution of this theory is show that the equilibrium in economic growth target and economic growth to natural rate, unemployment rate to natural rate is create the equilibrium in inflation and expected inflation. So the alternative policy stategy is increase in economic growth to the natural rate or decrease unemployment rate to the natural rate. From the side of inflation decomposition, increase in economic growth to the natural rate or decrease in unemployment rate to the natural rate is the same to maintaine the stabilizing in administered inflation, volatile food inflation, and traded goods inflation. From the side monetary policy, the stabilizing in volatile food inflation and traded goods inflation is created if increasing in monetary growth directed to small and medium business, because the small and medium business is absorpt more employment than the big business. From the side fiscal policy, the stabilizing in administered inflation is created if the government can eliminate the corruption in government projects. Eliminating the corruption in government projects will eliminate increase in price of strategic commodities, and it increase in social welfare.